MODEL-MODEL PENELITIAN DALAM PSIKOLOGI ISLAM - Amiq, Bahrun (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2008)
Human being is unique being and typical, therefore, when comprehending human being only by using scientific method, it will not be adequate enough, for that reason it has been raised a confidence method, ratiocination method, authority method, and intuition method as alternative method beside of scientific method. Furthermore, the existence of those alternative methods emerged four model of research that can be conducted in line to development of Islamic psychology.Keywords: scientific method and Islamic psychology method